Kebijakan Preventif Terhadap Tindak Pidana Korupsi Melalui Pendekatan Non-Penal - Bryant Montana; Hery Firmansyah (Jurnal Hukum Adigama, 2022)
Handling corruption in the Republic of Indonesia is more appropriate to use non-penal policies or those that are more concerned or inclined to efforts to prevent corruption which are directed at reducing opportunities to commit criminal acts of corruption, such as the report on the assets of state administrators, hereinafter referred to as LHKPN by every state institution, either executive, legislature and judiciary both at the central and regional levels so that state administrators get supervision in terms of assets so that this can reduce the potential for committing criminal acts of corruption. So far it has not been effective, besides that non-penal facilities can also reduce the number of corruption in Indonesia, therefore one form of prevention that can be intensified by the KPK is socialization about the dangers of corruption or by using n monitor all forms of cooperation carried out by every state institution, by attending every signing of cooperation agreements so that all budgets or funds launched can be accounted for properly, because if anti-corruption socialization continues to be intensified, it is not impossible to clean up the republic. Indonesia is from a corruption case which is dominated by state administrators, who should provide a good example of living the life of a nation and state to the community.